Penanganan Anak Berkebutuhan Khusus di KB-TK Hamemayu - Billah Faza Muhammadkan Bastian, Abda (ACIECE, 2019)
Handling Children with special needs in early childhood institutions is different from existingtherapies in psychologists and hospitals. Because early childhood institutions is an educationalinstitution, not a medical institution. The method of this research is a qualitative research (fieldresearch) with the collection of data through observation, interviews and documentation. ABKhandling menunujukkan research results in KB TK hamemayu provided through the provision ofstimulation. KB TK hamemayu designing lesson plan for children with special needs can interactwith each other. KB TK hamemayu also facilitate crew according to their ability